Crystallinity characterization of white matter in the human brain. (30th July 2021) - Teich, Erin G; Cieslak, Matthew; Giesbrecht, Barry; Vettel, Jean M; Grafton, Scott T; Satterthwaite, Theodore D; Bassett, Danielle S
Abstract: Human brain tissue is a heterogeneous material, consisting of soft outer grey matter tethered internally by stiffer cords of white matter. These white matter tracts conduct electrical impulses between grey matter regions, thereby underpinning neuronal communication. Understanding the material properties of white matter is thus crucial for understanding brain function generally. Efforts to assess white matter microstructure are currently hampered by the inherent limitations of reconstruction by diffusion imaging. Techniques typically represent white matter structures with single scalars that are often difficult to interpret. Here, we address these issues by introducing tools from materials physics for the characterization of white matter microstructure. We investigate structure on a mesoscopic scale by analyzing its homogeneity and determining which regions of the brain are structurally homogeneous, or 'crystalline' in the context of materials physics. We find that crystallinity provides novel information and varies across the brain along interpretable lines of anatomical difference, with highest homogeneity in regions adjacent to the corpus callosum, a large interhemispheric tract. Furthermore, crystallinity is markedly reliable across iterative measurement, yet also varies between individual human volunteers, making it potentially useful for examining individual differences in white matter along several dimensions including sex and age. We also parcellate white matter into 'crystal grains', or contiguous sets of voxels of high structural similarity, and find overlap with a common atlas of distinct white matter areas. Finally, we characterize the shapes of individual diffusion signatures through another tool from materials physics—bond-orientational order parameters—to locate fiber crossings and fascicles. Our results provide new means of assessing white matter microstructure on multiple length scales, and open multiple avenues of future inquiry involving soft matter physics and neuroscience.